Assistance in preparing financial reports for houses of worship with ISAK 35 standards in Sorong - M. Munzir; Z. Zulkifli; S. Sabaria; Risky Febri Wanda; Anetha Way; Pinkan Olivia Marchivanalia (Universitas Muhammadiyah Malang, 2024)
Houses of worship in Sorong City have not recorded financial reports according to standards and carry out bookkeeping using manual recording. Therefore, this activity aims to provide assistance in preparing financial reports for places of worship with the ISAK 35 standard. The method of implementing the service is carried out by giving presentations accompanied by direct interactive discussions between the implementing lecturer team and participants who come from members of the Religious Communication Forum in Sorong City. There are 30 partners involved in community service, consisting of 2 students, 3 lecturers, 5 administrators each of places of worship (churches, temples, mosques and monasteries) and 5 partners who assist in broadcasting worship. Based on the results of observations and interviews conducted by the service team using random sampling of participants, it can be concluded that implementing community service can provide new insights and knowledge for participants regarding the preparation of financial reports and an understanding of the importance of accurate and accountable reports. By taking part in assistance in preparing financial reports, apart from listening to explanations in preparing financial reports, the participants also held discussions regarding the obstacles faced in managing funds and reporting that is appropriate and easy to understand by users of financial reports and technology.